Effect of Intelligent Exercise Training on Lower Limb Rehabilitation in Children with Spastic Cerebral Palsy - Xuemei ZHANG; Meicong ZHANG; Liyang XIA; Yue YANG (康复学报)
Objective:To explore effects of intelligent exercise training on the rehabilitation for lower limbs in children with spastic cerebral palsy.Methods:A total of 98 children with spastic cerebral palsy were selected as the observation object. They were divided into control group and observation group according to the random number table method, with 49 cases in each group. The control group was given routine rehabilitation training. The observation group added intelligent exercise training on the basis of that in the control group. The motion sensitivity of the D and E areas was evaluated by the gross motor function measure-88(GMFM-88). The root mean square (RMS) value of the myoelectric signal on the surface of the gastrocnemius and adductor muscles was collected by surface electromyography tester. The balance function was evaluated by the Torso function scale (TIS) and the Berg balance scale (BBS).Results:There was no statistically significant difference in the GMFM-88 scores in D and E areas before treatment between the two groups (P> 0.05). After treatment, the GMFM-88 scores in the D area were (32.65±15.09), and the GMFM-88 scores in the E area were (44.32±18.02) in the observation group, which were significantly higher than those of (27.34±14.76) and (33.64±16.35) respectively in the control group (P< 0.05). There was no statistically significant difference in the myoelectric RMS of gastrocnemius and adductor muscles before treatment between the two groups (P> 0.05). The surface myoelectric RMS of gastrocnemius muscle was (8.43±1.65) μV and the surface myoelectric RMS of adductor muscle was (8.27±1.34) μV after treatment in the observation group, which were significantly lower than those of (12.38±2.76) μV and (11.89±2.26) μV in the control group (P< 0.05). There were no statistically significant differences in the balance of TIS and BBS scores before treatment between the two groups (P> 0.05). The TIS scores were (21.75±8.04) and the BBS scores was (45.23±18.23) after treatment in the observation group, which were significantly higher than those of (15.59±4.27) and (25.40±10.65) in the control group (P< 0.05).Conclusion:Compared with routine rehabilitation training, intelligent exercise training can significantly improve the exercise capacity and balance ability of children with spastic cerebral palsy, and can improve the muscle tension of the gastrocnemius and adductor children, and increase the stability in the food function. The curative effect is good and suitable for clinical application.